A full package of gains? Lay perspectives on a bioeconomic transition in Norway. (27th July 2021) - Farstad, Maja; Otte, Pia Piroschka
A sustainable bioeconomy based on production and consumption of food, products, and materials within healthy ecosystems is considered a promising response to global challenges like climate change and environmental degradation combined with a growing population. However, ultimately, it is the public as consumers and citizens who provide the market and governance for bioeconomic development. In this paper, we explore lay perspectives on a bioeconomic transition based on eight focus group interviews with lay people in Norway. Overall, we find that the public appears quite positive towards the idea of a bioeconomic transition due not only to expected global gains, but also to individual gains. The findings are relevant for the design of further bioeconomy-related policies aiming to achieve wide public acceptance.